CURRENT STATE AND PERSPECTIVES OF SATELLITE NAVIGATION APPLICATIONS IN ROAD TRANSPORT - Kalasova, Alica (Doprava a spoje, 2006)
The article describes new possibilities of how to use global satellite navigation system Galileo, that is made by European Union and its European Space Agency ESA. Compared to original army systems GPS and Glonass, Galileo is built to be used for civil applications. Galileo is built up in order to be compatible with current systems. This fact creates the assumption for the interactive back-up, the enhancement of visible satellites number and of required navigation performance demanded in transport and other applications, where is claim for extreme precision, integrity, availability and connection. Galileo offers various kinds of services - from open service through safety of life service, commercial service, public regulated service to the search and rescue service. These services will cover all sections of human activities, mainly the transport, in which the greatest expansion is expected in the area of automobile transport.